Making friends. Back to the drawing board - Gudsnuk, Kristen (Graphix, 2019)
Nearly everything was going great for Dany--she and Madison, still best friends; she has her magic sketchbook; and the new school year doesn't stink yet. When Dany gets overwhelmed with homework, though, she decides to use her magic to make a double of herself, accidentally unleashing supernatural havoc that threatens to ruin the upcoming school dance.